Ensino colaborativo e educação especial: uma revisão da literatura - Dalfré, Mariá Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Co-teaching is a service model that can be offered as a Specialized Educational Service for Special Education Students. This work aimed to identify and analyze national publications that empirically addressed educational inclusion through the influence of collaborative teaching in scientific articles, through the search of the terms "collaborative teaching", "bidocence" and "co-teaching" in combination with the term "educational inclusion" on the platforms Scientific Electronic Library Online (SciELO) and Coordination of Superior Level Staff Improvement (CAPES). Through the search, it was possible to identify twelve articles that, when analyzed, contributed to better understanding and presenting an overview of what has already been published about these subjects. Identifying knowledge gaps and contributing to the development of co-teaching theory over time in Brazil. The results showed that despite facing difficulties to be put into practice, collaborative teaching is an innovative and powerful proposal for promoting effective school inclusion, with the ability to help teachers and improve the quality of teaching for all students.

O ensino colaborativo é um modelo de serviço que pode ser ofertado como Atendimento Educacional Especializado (AEE) para estudantes Público-Alvo da Educação Especial (PAEE). Este trabalho teve como objetivo identificar e analisar publicações nacionais que abordaram empiricamente a inclusão escolar pelo viés do ensino colaborativo. A coleta dos artigos foi realizada com os termos de busca “ensino colaborativo”, “bidocência” e “coensino” em combinação com o termo “inclusão escolar”, nas plataformas Scientific Electronic Library Online (SciELO) e Periódico da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES). Foram identificados doze artigos que, ao serem analisados, colaboraram para a construção de um panorama do que já foi produzido sobre o tema, identificando lacunas e compreendendo o desenvolvimento da teoria colaborativa ao longo dos anos no país. Os resultados mostraram que, apesar de enfrentar obstáculos para ser colocado em prática, o ensino colaborativo é uma proposta inovadora e potente para a promoção de uma efetiva inclusão escolar, com capacidade de fortalecer o trabalho dos educadores e melhorar a qualidade do ensino para todos os alunos.
Collaborative teaching and special education: a literature review
Keywords: Educação especial; Educação inclusiva; Equipes de ensino; Ensino colaborativo; Special education; School inclusion; Collaborative teaching; Teaching teams